Reinstatement of extinguished fear by an unextinguished conditional stimulus - Halladay, Lindsay R.; Zelikowsky, Moriel; Blair, Hugh T.; Fanselow, Michael S. (Frontiers in Behavioral Neuroscience, 2012)
Anxiety disorders are often treated using extinction-based exposure therapy, but relapse is common and can occur as a result of reinstatement, whereby an aversive “trigger” can reinstate extinguished fear. Animal models of reinstatement commonly utilize a Pavlovian fear conditioning procedure, in which subjects are first trained to fear a conditional stimulus (CS) by pairing it with an aversive unconditional stimulus (US), and then extinguished by repeated presentations of the CS alone. Reinstatement is typically induced by exposing subjects to an aversive US after extinction, but here we show that exposure to a non-extinguished CS can reinstate conditional fear responding to an extinguished CS, a phenomenon we refer to as “conditional reinstatement.” Rats were trained to fear two CSs (light and tone) and subsequently underwent extinction training to only one CS (counterbalanced). Presenting the unextinguished CS (but not a novel cue) immediately after extinction reinstated conditional fear responding to the extinguished CS in a test session given 24h later. These findings indicate that reinstatement of extinguished fear can be triggered by exposure to conditional as well as unconditional aversive stimuli, and this may help to explain why relapse is common following clinical extinction therapy in humans. Further study of conditional reinstatement using animal models may prove useful for developing refined extinction therapies that are more resistant to reinstatement.